FOREIGN EXPERIENCE IN GUIDING STUDENTS TO THE PROFESSION (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In this article, based on the needs of the times, the form of "dual education" was introduced, which allows young people to study and earn at the same time, to connect educational programs with the demand for life, to introduce foreign educational programs, to improve internal and external qualifications of graduates. measures to improve the quality of ensuring recognition in the foreign market are provided.